Too hot to handle? The impact of the 2023 marine heatwave on Florida Keys coral - Neely, Karen L.; Nowicki, Robert J.; Dobler, Michelle A.; Chaparro, Arelys A.; Miller, Samantha M.; Toth, Kathryn A. (Frontiers in Marine Science, 2024)
The summer 2023 marine heatwave was the most severe on record for Florida’s Coral Reef, with unprecedented water temperatures and cumulative heat stress leading to 100% coral bleaching. An existing fate-tracking program of over 4200 brain and boulder coral colonies across five offshore and four inshore reefs allowed for analyses of bleaching-related mortality and diseases through the event. Across the vast majority of assessed corals, there was no partial or full mortality as a result of the 2023 bleaching event. At seven of the nine sites, only 0 – 2% of fate-tracked colonies experienced any mortality. The other two sites, both inshore, had the highest cumulative heat stress and did experience substantial bleaching-related mortality. However, acute mortality at one of them began at relatively low cumulative heat stress, suggesting death was the result of exceeding thermal maxima rather than bleaching-related resource depletion. At the two most impacted sites, 43% and 30% of all monitored corals died, but mortality varied among species: brain corals fared worse than boulder corals. The health status of corals before the bleaching event had little impact on whether they exhibited mortality during the event. At three sites, we observed unusual lesions on Orbicella faveolata colonies shortly after color returned to the corals; these were only present for a few months, but on some colonies led to substantial tissue loss. Though not part of the monitoring program, we also observed local extinctions of Acroporid corals at most sites, as well as local extinctions of octocorals at three inshore reefs. Though most reef-building corals survived the 2023 marine heatwave in the Florida Keys, continually rising temperatures are likely to make these temperature regimes more common. We encourage future research on why the brain and boulder corals fared differently at highly-impacted sites, and on what the unusual O. faveolata lesions are. Our results also provide perspective on how restoration strategies, particularly those focused on species likely to die under current and future climate regimes, might prioritize species likely to survive. Finally, these results highlight the importance of fate-tracking individuals of different species and in different geographies and habitat types through disturbance events.